2006
DOI: 10.4049/jimmunol.177.11.7698
|View full text |Cite
|
Sign up to set email alerts
|

Control of Memory CD4 T Cell Recall by the CD28/B7 Costimulatory Pathway

Abstract: The CD28/B7 costimulatory pathway is generally considered dispensable for memory T cell responses, largely based on in vitro studies demonstrating memory T cell activation in the absence of CD28 engagement by B7 ligands. However, the susceptibility of memory CD4 T cells, including central (CD62Lhigh) and effector memory (TEM; CD62Llow) subsets, to inhibition of CD28-derived costimulation has not been closely examined. In this study, we demonstrate that inhibition of CD28/B7 costimulation with the B7-binding fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
123
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(131 citation statements)
references
References 61 publications
8
123
0
Order By: Relevance
“…In support of the latter possibility, Lakkis and colleagues (51,52) reported that allospecific memory but not naive T cells can home directly to the allograft to proliferate and mediate rejection independently of secondary lymphoid organs. Finally, the observation that the majority of the cells infiltrating the allografts are CD8 + TEMs, and of memory CD8 + TEMs being more resistant to costimulation blockade (11,45,53,54), are consistent with CD8 + TEMs as the mediators of CTLA4-Ig-resistant rejection. The accumulation of memory CD8 + T cells in the allograft suggested that inhibition of T cell infiltration into the allograft would promote graft survival.…”
Section: Cd4mentioning
confidence: 60%
See 1 more Smart Citation
“…In support of the latter possibility, Lakkis and colleagues (51,52) reported that allospecific memory but not naive T cells can home directly to the allograft to proliferate and mediate rejection independently of secondary lymphoid organs. Finally, the observation that the majority of the cells infiltrating the allografts are CD8 + TEMs, and of memory CD8 + TEMs being more resistant to costimulation blockade (11,45,53,54), are consistent with CD8 + TEMs as the mediators of CTLA4-Ig-resistant rejection. The accumulation of memory CD8 + T cells in the allograft suggested that inhibition of T cell infiltration into the allograft would promote graft survival.…”
Section: Cd4mentioning
confidence: 60%
“…While some studies suggest that memory T cells do not require costimulation for reactivation, others have reported that costimulation remains necessary for their recall activation and expansion in vivo (40)(41)(42)(43)(44)(45). By carefully tracking endogenous donor-specific T cells using the IFN-γ ELISPOT assay as well as with fluorescently labeled 2W:I-A b and OVA:K b multimers, we observed that CTLA4-Ig was able to prevent the expansion of donor-specific T cells in sensitized mice.…”
Section: Cd4mentioning
confidence: 99%
“…In vitro activation of memory T cells in the absence of CD28 engagement by B7 ligands was also normal [37,41] The CD28/B7 costimulatory pathway was thus generally considered dispensable for memory T cell responses. However, Ndejembi et al [42] reported that, although recall functions like up-regulation of activation marker expression on memory CD4 cells are independent of CD28 costimulation, optimal IL-2 production and, most importantly, expansion of memory CD4 T cells required CD28 costimulation. Interestingly, our findings suggest that signaling through CD28 alone can be sufficient for activation and expansion of memory CD4 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…We here provide a proof-of-concept that subtle alterations in T-cell function caused by dysregulation of single immune-regulatory molecules might explain interindividual, as well as intraindividual, changes in lesion topography and phenotypes of MS. One plausible cause for such interindividual variations could be the presence of single nucleotide polymorphisms in immune-relevant genes in individuals (38). On the other hand, especially, intraindividual changes might be caused as bystander effects due to altered expression of costimulatory or coinhibitory molecules in the context of bacterial or viral infections (39,40). Following this line, such changes in expression levels of immune-regulatory molecules or adhesion molecules with their consequences with regard to T-cell invasion into the CNS might also account for so far unexplained decreases in the individual treatment response during the course of therapy, as observed in the context of natalizumab treatment.…”
Section: Discussionmentioning
confidence: 99%